Study the spectroscopic characteristics of Rhodamine B Dye in Ethanol and Methanol mixture and Calculation the Quantum Efficiency (Baghdad Science Journal, 2012)
The effect of ethanol and methanol solvent, and their mixture has been studied on the absorption and fluorescence spectra of laser dye Rhodamine B at concentration of (10-4) Molar at room temperature. The molar absorption coefficient has been determined for mixture which was (3.223) at wave number (18181.8 cm-1), Also the Quantum Efficiency of the two solvents (ethanol and methanol) and their mixture have been calculated ,which was for mixture spectrum (38.94%) and it was larger comparing with other and solvents. The characteristics of spectrum has been determined by calculating (??) of absorption spectrum for the solvents and its mixture at maximum wave number ( ) cm-1 depending on solvent polarity and the transitions between molecular energy levels in each solvent of Rhodamine B dye .